Effectiveness Of The Use Of Madras E-Learning Applications During The Covid Pandemic 19 (Case Study at Madrasah Aliyah Negeri 2 Bandung) - M.Tajudin Zuhri; Budie Agung; Khalid Ramdhani (At-Ta'dib, 2020)
This study aims to identify the effectiveness of the use of madrasah e-learning applications and determine the inhibiting and supporting factors of the implementation of e-learning applications as learning media. This research is quantitative. Data collected through questionnaires, interviews, and observations, then the data were analyzed descriptively. Respondents from this study were teachers and students of Madrasah Aliyah Negeri 2 Bandung, who were directly involved with learning to utilize e-learning applications. The results showed that the affective component of the use of e-learning madrasas tended to be less effective. It was shown from the view of the students 'activeness in utilizing e-learning madrasas in learning which showed an average of 76.46 less effective, students' understanding of teaching materials after using the application that is, 35.7% never understood, 55.6 sometimes understood, and only 7.1% understood the material taught through the madrasah e-learning application. Overall it can be concluded that the implementation of madrasah e-learning learning as e-learning media in MAN 2 Bandung is less effective, due to several factors of its implementation including the lack of HR related to madrasah e-learning, network problems, and quota but MAN 2 Bandung is very effective in online learning due to several factors of its implementation including the lack of human resources related to e-learning madrassas, network problems, and quotas but MAN 2 Bandung is very effective in online learning using other applications besides madrasa e-learning applications such as google classroom, google form, zoom, Whatsapp Group, kahoot, and Quizizz.